CARBON QUANTUM DOTS (CQDS) from RAMBUTAN and PANDAN LEAVES for CU2+ DETECTION - Laksmi Dewi Kasmiarno; Andini Fikarda; Reforny Kristianti Gunawan; Isnaeni Isnaeni; Supandi Supandi; Nonni Soraya Sambudi (Waste Technology, 2021)
A facile and eco-friendly process for the synthesis of carbon quantum dots (CQDs) was carried out via hydrothermal and microwave treatment using Rambutan and Pandan leaves as carbon sources. The effects of synthesis methods on the optical and physical properties of CQDs, and the sensing activity of CQDs through Cu2+ detection are presented in this study. From the analysis, the band-gap energies of CQDs are found to be ranging from 2.52 to 3.51 eV. The CQDs solutions exhibit significant fluorescence property, in which bright cyan fluorescence can be detected under Ultraviolet (UV) light irradiation at wavelength of around 405 nm. The CQDs synthesized from Pandan and Rambutan leaves using hydrothermal method show quantum yield (QY) values at around 2.46% and 2.70%, respectively.  The FT-IR analysis recorded existing functional groups on the surface of CQDs to be of hydroxyl and carbonyl groups, which can serve as adsorption sites for the detection of Cu2+. Furthermore, this study indicates that CQDs emission from Pandan and Rambutan leaves using hydrothermal method shows the best turn-off behavior when detecting the presence of Cu2+ with minimum limit of detection (LoD) as low as 123 µM.